Principal Leadership Policy in Improving Effectiveness Performance Teacher at Raja Ampat Elementary School - Sumual, Tinneke E. M.; Sumual, Herry; Sauyai, Stanly F M; Rambitan, Maya C.; Wuwungan, Hansje T.; Tendean, Sherly D. (JR Education, 2024)
This research is intended to describe 1) leadership policies to increase the effective performance of teachers on a school Base; 2) constraint policy leadership which obstructs the effective performance of teachers inside; and 3) solutions based on leadership theory that can improve the effectiveness of teacher performance. This research uses qualitative research methods and studies cases done in Raja Ampat Elementary School with 3 informants which consists of head schools, civil servants, and non-PNS teachers. Research findings show that 1) policy the principal's leadership in solving school problems by recruiting additional teachers, sharing teaching hours with newly hired teachers, and providing administrative tasks to administrative workers to increase performance effectiveness Teacher. Policy head school influences the performance of several teachers; 2) constraint school management faced by school principals in decision making caused by several teacher and worker administration with no discipline, no capable, and unskilled; and 3) solutions created by the principal to improve the effectiveness of teacher performance includes teacher participation in every school activity can increase performance Teacher. To increase performance teacher, teachers which more active and creative are given additional financial rewards while teachers who cannot afford it and have no skilled are sent for follow training on knowledge, skills, and enhancement competence.